Mobiliario recreativo para el desarrollo físico y cognitivo de niños en etapa preescolar para el parque infantil del sector Techo Propio, ciudad de Ambato - Vintimilla Cordero, John Michael (2023)
This graduation project's main objective is the design of recreational furniture for the physical and cognitive development of preschool children in the Techo Propio sector. It arises from the lack of suitable entertainment options that do not adequately promote physical and cognitive development. Currently, the park has a prefabricated play equipment where safety takes precedence over stimulation. Consequently, this can lead to negative effects on the health and well-being of preschool children, such as motor development delays, cognitive difficulties, low self-esteem, social problems, poor academic performance, and even cardiovascular diseases. Therefore, the use of new forms and materials is proposed to create a connection with the activities they engage in daily and the toys they use in their everyday lives. This aims to encourage an active lifestyle and generate opportunities for children to participate in age appropriate activities. In this way, it would contribute to improving their social development, guiding them towards play as a learning tool that fosters physical, sensory, mental, and creative activity. This would be achieved by establishing play as a habit. The project adopts a qualitative and quantitative approach. To support and develop this work, sources of documentary and field research have been used.